Ligand influences on homoleptic Group 12 m-terphenyl complexes - Blundell, Toby J.; Hastings, Fiona R.; Gridley, Benjamin M.; Moxey, Graeme J.; Blake, Alexander J.; Lewis, William; Kays, Deborah L. (Royal Society of Chemistry, 2014)
Three m-terphenyl ligands 2,6-Ar2C6H3 – [Ar = 2,6-Me2C6H3 (2,6-Xyl); 3,5-Me2C6H3 (3,5-Xyl); 2,3,4,5,6-Me5C6 (Pmp)] have been used to stabilise three series of two-coordinate Group 12 diaryl complexes; (2,6-Ar2C6H3)2M [M = Zn, Cd, Hg; Ar = 2,6-Xyl 1-3; 3,5-Xyl 4-6; Pmp 7-9], where differing steric demands on the metal centres are imparted. These are the first homoleptic d-block complexes featuring any of these ligands. Complexes 1-9 have been characterised in solution and the solid state; the analysis of structural changes produced by differences in ligand properties is reported. In particular, complexes 4-6 show smaller C–M–C bond angles and contain secondary ligand interactions that are not seen in the analogous complexes 1-3 and 7-9.